Growth problems in youth elite sports. Social conditions, athletes` experiences and sustainability consequences - Schubring, A.; Thiel, A. (Reflective Practice. International and Multidisciplinary Perspectives, 2014)
In elite sports, growth and maturation are important preconditions for advancing performance and athletic development. However, intensive training at an early age may contribute to the occurrence of growth problems in adolescent athletes. In the elite sport context, growth problems are most often considered biomedical phenomena or reduced to individual disposition. Consequently, their social origins have gone unexamined. Drawing on interviews with German youth elite athletes, we outline how social conditions (e.g. discipline-specific body ideals and early selection) contribute to the genesis of growth problems. Furthermore, we offer insight into athletes` problematic growth experiences and analyze them as a risky condition for successful socialization into elite sports. In adopting the language of sustainability, we understand growth problems as an example of `unsustainability`. We examine how they affect athletes` individual sustained development, safety, well-being and capacity building, and also question the organizational sustainability of high performance sports. We conclude by outlining the implications for coaching practices and the adjustments needed in the organization of youth elite sports. Fulltext request: https://www.researchgate.net/publication/263598744_Growth_problems_in_youth_elite_sports._Social_conditions_athletes_experiences_and_sustainability_consequences1